Understanding the genetic control and physiological traits associated with rhizosheath production by barley (Hordeum vulgare) - George, Timothy S (The New phytologist, 2014)
© 2014 Crown copyright Published with the permission of the Controller of HMSO and the Queen's Printer for Scotland.